The double sheath on cathodes of discharges burning in cathode vapour - Benilov, M. S. (2022)
The model of a collisionless near-cathode space-charge sheath with ionization of atoms emitted by the cathode surface is considered. Numerical calculations showed that the mathematical problem is solvable and its solution is unique. In the framework of this model, the sheath represents a double layer with a potential maximum, with the ions which are produced before the maximum returning to the cathode surface and those produced after the maximum escaping into the plasma. Numerical results are given in a form to be readily applicable in analysis of discharges burning in cathode vapour, such as vacuum arcs. In particular, the results indicate that the ion backflow coefficient in such discharges exceeds 0.5, in agreement with values extracted from the experiment.